2016
DOI: 10.1007/s13187-016-1083-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and Success of a 21st Century Cancer Education Program at the University of Louisville

Abstract: Cancer incidence, morbidity, and mortality in the Commonwealth of Kentucky are among the highest in the nation. The University of Louisville was the recipient of a National Cancer Institute (NCI)-funded cancer education program grant in 1975 under the leadership of Dr. Norbert Burzynski. A new and totally redesigned performance-based University of Louisville Cancer Education Program was funded by NCI in 2011 to recruit and motivate outstanding undergraduate and health professional students to pursue further tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In comparison to other, similar high school and undergraduate student cancer research experience programs, the ACTION Program appears to be achieving similar if not more favorable outcomes. For example, a 2018 publication on the University of Louisville's (UofL) Cancer Research program reported that approximately a third of the students who participated in the program went on to pursue advanced education (beyond undergraduate) in health-science related fields (Hein & Kidd, 2018). It is important to note that UofL's program is not a direct comparison since it does not include the academic year research component and the total number UofL participants (n=121) was also significantly higher than the ACTION Program to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other, similar high school and undergraduate student cancer research experience programs, the ACTION Program appears to be achieving similar if not more favorable outcomes. For example, a 2018 publication on the University of Louisville's (UofL) Cancer Research program reported that approximately a third of the students who participated in the program went on to pursue advanced education (beyond undergraduate) in health-science related fields (Hein & Kidd, 2018). It is important to note that UofL's program is not a direct comparison since it does not include the academic year research component and the total number UofL participants (n=121) was also significantly higher than the ACTION Program to date.…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Institute's (NCI) Youth Enjoy Science (YES) Research Education Program funds nonprofit and government-based research programs with the dual goal of increasing cancer knowledge and awareness among underrepresented students while also preparing these students to participate in careers in biomedical research (NCI, 2021b). Programs funded by the NCI and other cancer research training programs have been shown to increase awareness of cancer and cancer prevention methods (Cameron et al, 2012); increase interest in cancer research (Hein & Kidd, 2018); increase interest in medical and/or cancer-related careers (Alfred et al, 2011); and produce a high number of students pursuing and completing medical, professional, and doctoral programs (Alfred et al, 2011;Gronemeyer, 2011;Hein & Kidd, 2018). These programs for high school and undergraduate students have primarily focused on promoting cancer research training to underrepresented racial minority youth populations and/or students from urban areas (Alfred et al, 2011;Hein & Kidd, 2018;Qua et al, 2020).…”
Section: Introductionmentioning
confidence: 99%